Islamic Spirituality and Subjective Well-Being among Generation Z - Fajri Fauzan Azhari; Nailah Dhiya Ulhaq; Ghina Ilma Alia; Arsyaddhia Edra Rustam; Nita Trimulyaningsih (Green Publisher, 2025)
Generation Z faces significant psychological and emotional challenges that affect their subjective well-being. In the digital age, constant social media exposure and online comparison contribute to lower subjective well being. Research in Indonesia shows that spirituality plays an important role in improving subjective well-being. The purpose of this study is to examine the relationship between Islamic spirituality and subjective well-being. A quantitative correlational approach was conducted on Muslim Gen Z who are in the age range of emerging adults (n = 171, 64 males and 107 females, aged 18-25 years). This study used the Islamic spirituality scale, which refers to Swinton's theory, and the Subjective well-being scale, which was measured using two measuring instruments, namely the Satisfaction With Life Scale (SWLS) and the Positive Affect Negative Affect Scale (PANAS). Pearson correlation analysis showed that there is a highly significant positive correlation between Islamic spirituality and subjective well-being (r = 0.530, p < 0.001), with the meaning aspect in the Islamic spirituality variable providing the largest positive contribution to respondents' subjective well-being, which is 30.5%. Then there are differences in the level of subjective well-being when viewed from gender where men have a higher level of subjective well-being than women. Islamic spirituality can be applied in the form of therapy, counseling or guidance and counseling to improve subjective well-being in Gen Z, especially in facing difficult times and existential crises.